(untitled) (Conferencea, 2022)
The article describes the advantages and disadvantages of students’ self-guided work through creation of PowerPoint presentations for the development of their linguistic and informational competence. The merits of this kind of work prevail over the demerits and include the development of information analysis, scientifi c research activities, writing, speaking and listening comprehension skills, increasing motivation of studying English